Resfriar a cabeça aumenta a velocidade durante a corrida intermitente de intensidade autorregulada sob o sol, em condições fisiológicas semelhantes - Lucas Leite Lima (2011)
Fatigue is defined as a decrease in force production or an inability to regenerate the original strength and can be understood as a mechanism of protection against risks to homeostasis. An important factor for the onset of fatigue during exercise is heat environment. Some studies show that cooling the head can reduce the physiological stress and reduce fatigue in situations of fixed intensity exercise in the heat but little is known about the effects of head cooling on performance during the race for self-regulated intensity. The aim of this study was to investigate the effect of cooling the head in performance, physiological stress and thermoregulatory responses in self-paced exercise under the sun. For that participated in the study 10 male volunteers, healthy and physically active (aged 24 ± 2 years, VO2max 47.0 ± 3.9 ml.km-1.min-1, body mass 76.3 ± 6.4 kg , height 180.6 ± 5.7 cm, body surface area 1.96 ± 0.08 m2, sum of skinfolds 107 ± 46.2 mm). The volunteers ran a total of 6 km in four steps of 1.5 km with intervals of 3 minutes as fast as they could - with (CRC) or without cooling of the head (control group - "CON"). Cooling the head increased the average running speed by 5.2% with no change: of the physiological strain index, thermoregulatory variables and perceived exertion. The average temperature of the head was smaller and the thermal comfort was improved in the CRC. Moreover, the cooling of the head also reduced heart rate during the pre-exercise and during exercise the whole. The total sweating did not differ between situations, but the sweating of the forehead was lower in CRC situation. Of the regions measured (forehead, chest, arm and thigh), sweating thigh was the lowest. Conclusion: the cooling of the head was able to improve performance during intermittent running intensity performed self-regulated under the sun, without changing the physiological strain index and thermoregulatory responses.